Design of Capacitated Emergency Service System - Lydia Gabrisova; Jaroslav Janacek (Communications - Scientific letters of the University of Zilina, 2015)
Optimal design of the emergency service systems mostly consists in the decisions on a deployment of service centers, which provide the nearest system users with the associated service. As the demand for emergency service occurs randomly, the nearest service center may be occupied by servicing some previous demand and thus the current demand must be serviced from some more distant available service center. This phenomenon is dealt with in this paper where the center capacity is considered in the service system design to mitigate frequency of the above–mentioned events. For this purpose, two approaches to the capacitated service center deployment were suggested, implemented and tested on several benchmarks to give a relevant comparison of them.